O suporte social e o impacro na família de pacientes candidatos a transplante de fígado - Clerison Stelvio Garcia (2013)
Introduction: Many liver diseases can end up requiring liver transplantation, because they cause progressive liver lesions and develop cirrhosis. This condition brings changes to the patients quality of life and social roles. It is important to assess social support and the impact on the family of patients who undergo liver transplantation. Objective: To evaluate social support and the impact on the patients family, during the time preceding liver transplantation, in the Hospital of Clinics of the Universidade Federal de Minas Gerais (HC-UFMG). Participants and Method: We accomplished a transversal, quantitative study, among the patients who were on the waiting list for liver transplant in the HC-UFMG. This research was developed in the following steps (1) Collection of demographic and clinical characteristics. (2) Evaluation of social support using the Portuguese version of the Social Support Network Inventory (SSNI-Portuguese). (3) Collection of data for evaluation of the impact on the patients family, using the Portuguese version of the Zarit Caregiver Burden Interview form (ZBI). Data were analyzed by descriptive, comparative and correlational statistics (Kruskal- Wallis and Spearman correlation), using the SPSSversion 12. Results: Among the 119 patients, the mean value for age was 50 years, 87 (73.1%) were males, 83 (69.8%) were married or lived with a partner, 60% had 8 years or less of education, and only 11% worked over 30 hours per week. In the sample, 28% had liver disease caused by alcohol or virus. The Meld score had a mean of 16.7 (SD 4.9), median of 16 (6 to 34). Among the participants, 56% did not have encephalopathy in the past month. Only 12% said receiving any kind of psychotherapy, and the most prevalent etiology was depression. The mean value for the global impact on the family scale was 28.62 ± 13.26, median was 26 points (range = 01 to 58) and Cronbach`s alpha = 0.814. Mean value for the global social support scale was 37.29 ± 3.88, median of 37.37 (range = 25 to 45) and Cronbach`s alpha = 0.75. Educational level was positively related with social support and negatively related with impact; age bellow 30 years was positively related with support; patients referred for liver transplant because of ethylic cirrhosis had lower social support, and patients with concurrent diseases presented lower social support and higher impact on their families. Conclusion: Higher educational level, absence of concurrent diseases, and having feelings of joy were related to a lower impact on the family and higher social support. Furthermore, higher impact on the patients family was related to the use of more medications. Patients who had ethylic cirrhosis had the lowest social support.